Virtual reality (VR) and augmented reality (AR) in libraries and museums. Issue 5 (25th June 2018) - Oyelude, Adetoun A.
Abstract : Purpose: This edition of this study aims to focus on augmented reality (AR) and virtual reality (VR) in libraries and museums, as seen from the internet cyber sphere including blogs. It takes a look at the first quarter of 2018 and analyzes the trending issues within the period, highlighting examples of some institutions that make use of VR and AR. The advantages of the use of VR, AR and sometimes mixed reality are also pointed out. Design/methodology/approach: Libraries, archives and museums are increasingly using AR/VR technologies in their service delivery because it is trending. The year 2018 is expected to be huge for VR technology. Findings: Facebook is the largest investor in AR and VR, and because Facebook is also extremely popular, many are opportune to have a go at VR and AR through the use of the Facebook social media platform. Originality/value: VR "involves using 3D graphics and advanced interactions to immerse a real-world user in a simulated environment", by the description of the University of Indiana University, Bloomington's Blogspot. AR stands for extended reality and actually, in technical terms, means a combination of virtual and real reality (UWS, 2018). Both VR and AR, 3D printing and other technologies have altered how people live and work.